2016
DOI: 10.1103/physreva.94.013811
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation theory for graphene-integrated waveguides: Cubic nonlinearity and third-harmonic generation

Abstract: We present perturbation theory for analysis of generic third-order nonlinear processes in graphene integrated photonic structures. Optical response of graphene is treated as the nonlinear boundary condition in Maxwell equations. The derived models are applied for analysis of third harmonic generation in a graphene coated dielectric micro-fibre. The efficiency of up to few percent is predicted when using sub-picosecond pump pulses with energies of the order of 0.1nJ in a sub-millimeter long fibre, when operatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…We follow the standard approach (see, e.g. [65]) and take E k eff ( ) to be the average of the fields above and below the 2D layer,…”
Section: Suspended 2d Layermentioning
confidence: 99%
See 1 more Smart Citation
“…We follow the standard approach (see, e.g. [65]) and take E k eff ( ) to be the average of the fields above and below the 2D layer,…”
Section: Suspended 2d Layermentioning
confidence: 99%
“…It has been pointed out that for weakly coupled 2D layers the atomic spacing between the layers should guarantee coherent radiation from the layers [8,60]. Despite many investigations using standard software [22,61,62], and nonlinear boundary conditions [63][64][65][66], there is still no systematic treatment of the response of graphene, taking into account its 2D nature, which could later be generalized to treat multilayer samples.…”
Section: Introductionmentioning
confidence: 99%
“…The linear band structure of graphene has been identified as the origin of the exceptionally strong nonlinear optical response of graphene [33]. Third-order nonlinearities are found to be remarkably strong in single-layer graphene [34][35][36], with * mazs@pku.edu.cn † czhang@uow.edu.au nonlinear susceptibilities several orders of magnitude above those of transparent materials and of the same order as in other resonant materials such as metal nanoparticles. Higherorder harmonic generation (HHG) in single-layer graphene has also been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nonlinear optical properties of graphene have attracted much attention because recent investigations have shown that the third-order nonlinear optical response of the single-atom-layer graphene is particularly strong [1][2][3][4][5]. Many studies have focused on such an aspect, such as saturable absorption [6][7][8][9][10][11], optical limiting [12,13], two-photon absorption [14], four-wave mixing (FWM) [1,15,16], and third-harmonic (TH) generation [17][18][19][20][21][22][23][24]. This allows one to employ graphene in active photonic devices with improved functionality [3,18,19].…”
Section: Introductionmentioning
confidence: 99%